2018
DOI: 10.3390/nano8080603
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Graphene Oxides as Possible Foam Stabilizing Agents for CO2 Based Enhanced Oil Recovery

Abstract: Graphene oxide, nanographene oxide and partially reduced graphene oxide have been studied as possible foam stabilizing agents for CO2 based enhanced oil recovery. Graphene oxide was able to stabilize CO2/synthetic sea water foams, while nanographene oxide and partially reduced graphene oxide were not able to stabilize foams. The inability of nanographene oxide for stabilizing foams was explained by the increase of hydrophilicity due to size decrease, while for partially reduced graphene oxide, the high degree … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…These experiments were performed at ambient pressure and temperature conditions. The primary goal of this work was to investigate the possibility of using conventional oilfield chemicals as agents for mobility control of hydrogen, similar to other studies reported for CO 2 in the literature. ,, …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…These experiments were performed at ambient pressure and temperature conditions. The primary goal of this work was to investigate the possibility of using conventional oilfield chemicals as agents for mobility control of hydrogen, similar to other studies reported for CO 2 in the literature. ,, …”
Section: Introductionmentioning
confidence: 87%
“…The primary goal of this work was to investigate the possibility of using conventional oilfield chemicals as agents for mobility control of hydrogen, similar to other studies reported for CO 2 in the literature. 33,38,39 2. MATERIALS AND METHODS 2.1.…”
Section: Introductionmentioning
confidence: 99%
“…rGO with the content of 13–22% could not stabilize the foam, which was different from the results obtained by Liu. This may be due to the high reduction degree of the particles, and the increase of oxygen content would enhance the hydrophilicity and reduce the CO 2 -affinity [ 113 ].…”
Section: Application In the Upstream Oil And Gas Industrymentioning
confidence: 99%
“…39 Using NPs in synergy with surfactants increased the strength of the generated foam and decreased the amount of surfactant used. 47,53 Gas bubbles in nanofluid-based foam were smaller, more uniform, and more stable against coalescence and coarsening compared to those in surfactant-based foam. 39 Carbonaceous NPs have also been utilized as foam stabilizers.…”
Section: Introductionmentioning
confidence: 99%